Q is for quark : a science alphabet book - Schwartz, David M.; Doner, Kim, 1955- (Berkeley, Calif. : Tricycle Press, 2001)
Discusses twenty-six scientific concepts, one for each letter of the alphabet.
Includes index.
School Library Journal
8.0
5-8
Keywords: Science -- Miscellanea -- Juvenile literature; Alphabet -- Juvenile literature; Science -- Miscellanea; Alphabet; Science -- Miscellanea; Alphabet